Case report: Successful administration of cariprazine in a young, severely ill patient with recurrent relapses of schizophrenia and persistent negative symptoms - Vrublevska, Jelena (Frontiers in Psychiatry, 2023)
The present case report describes a young man diagnosed with schizophrenia and presents a “revolving door” (RD) phenomenon. He was hospitalized in an acute psychiatric clinic three times in 1 year. After each hospitalization, he was discharged with incompletely reduced psychotic symptoms, persistent negative symptoms, low functioning, lack of insight, and adherence. He had an insufficient response to maximally tolerated doses of antipsychotic monotherapy with haloperidol and risperidone. Moreover, his treatment was complicated due to the low accessibility of long-acting injectable atypical antipsychotics (LAI) in the country and his refusal of the only available atypical LAI paliperidone palmitate and refusal to take clozapine. Due to limited alternatives, the decision to administer combinations of antipsychotics was made. Since his diagnosis, he received several combinations of antipsychotics, i.e., haloperidol + quetiapine, risperidone + quetiapine, haloperidol + olanzapine, risperidone + olanzapine, but without sufficient clinical effectiveness. Although combinations of antipsychotics reduced his positive symptoms to some degree, persistent negative symptoms and extrapyramidal side effects were observed. After initiating cariprazine, which was combined with olanzapine, improvement in the patient’s positive symptoms, negative symptoms, and overall functioning was detected. The combination of medications mentioned above facilitated the therapeutic alliance, thus providing control over the symptoms and preventing psychiatric hospitalizations.